Chronic exposure to polyethylene terephthalate microplastics induces gut microbiota dysbiosis and disordered hepatic lipid metabolism in mice - Tao Lu; Huan Liu; Xiaoqing Yuan; Desheng Li; Guanqing Zhang; Yue Wang; Qiqiang Xie; Xinhao Wang; Jingjian Chi; Zhenzhen Wang; Shaoping Wang; Yanling Gao; et al. (Ecotoxicology and Environmental Safety)
Despite the widespread presence of polyethylene terephthalate microplastics (PET MPs) in the environment, their biotoxicity, target organs, and underlying toxicological mechanism remain poorly understood. In this study, irregularly shaped PET MPs resembling those commonly found in natural environment were selected. Mice were orally administered different amounts of PET MPs (0, 5, 50, and 500 μg/day) for 17 weeks, after which relevant pathological and biochemical indicators were assessed. The results confirmed, for the first time, that PET MPs can induce oxidative stress, lipid accumulation, and apoptosis in liver cells, resulting in structural damage and functional abnormalities in the liver. Additionally, metabolomic analysis was combined with intestinal microbiota profiling to elucidate the potential toxicological mechanism. The data revealed that chronic exposure to high doses of PET MPs substantially altered the diversity of the intestinal flora. In particular, the relative abundances of Parasutterella, Muribaculum, and Turicibacter increased, accompanied by elevated levels of lipid metabolites such as linoleic acid, taurocholic acid, and sphingosine. These changes disrupted metabolic processes and accelerated lipid deposition in the mouse liver, thereby inducing hepatotoxicity. Moreover, a validation experiment confirmed that depletion of the gut microbiota in mice alleviated PET MPs-induced hepatotoxicity. These findings provide new insights into the toxicity of PET MPs in humans and other mammals.